PEMBELAJARAN PAI KONTEKSTUAL DI SMP AR-RAHMAT BOJONEGORO - MUTAMAKIN MUTAMAKIN (STAI Ma'had Aly Al-Hikam Malang, 2020)
This research focuses on the implementation of contextual Islamic Education learning at SMP Al-Rahmat Bojonegoro. The results of this study indicate: 1) The paradigm shift of Islamic Education teachers from the conventional paradigm (students as objects), to the new paradigm of students as learning subjects. Teachers have an understanding that learners' knowledge always develops according to experience; 2) Contextual learning activities are carried out in a conducive learning atmosphere, the assessment is carried out as a whole; cognitive, affective, and psychomotor. 3) Students have a good response to this contextual learning. With the perception and understanding of the importance of contextual learning from teachers, plus a positive response from students, the implementation of contextual Islamic Education learning can increase students' motivation to learn and improve learning outcomes and provide students with social life skillsFokus Penelitian ini adalah pelaksanaan pembelajaran PAI kontekstual di SMP Al-Rahmat Bojonegoro. Hasil dari penelitian ini menunjukkan: 1) Perubahan paradigma Guru PAI dari paradigma konvensional (peserta didik sebagai objek), kepada paradigma baru peserta didik sebagai subyek belajar. Guru memiliki pemahaman bahwa pengetahuan peserta didik selalu berkembang sesuai dengan pengalaman; 2) Kegiatan pembelajaran kontekstual dilaksanakan dengan suasana pembelajaran yang kondusif, penilaian dilakukan secara menyeluruh; kognitif, afektif dan psikomotor. 3) Peserta didik memiliki respon yang baik terhadap pembelajaran kontekstual ini. Dengan adanya persepsi dan pemahaman pentingnya pembelajaran kontekstual dari para guru, ditambah respon positif dari peserta didik, implementasi pembelajaran PAI kontekstual dapat meningkatkan motivasi belajar peserta didik dan meningkatkan hasil akhir belajar serta memberi bekal peserta didik dengan sosial life skill.